Shakespeare's Romeo and Juliet : a graphic novel - Barlow, Steve, ....-; Skidmore, Steve, ....-; Wei Tan Shian, Wendy, ....- (London : Franklin Watts, 2022)
Shakespeare's Romeo and Juliet like you've never seen it - or read it - before, in pitch-perfect graphic novel form
Classics in Graphics flings wide the doors of literature for all to enter and understand. Get pulled into the feast of pictures and words, experiencing the famous themes and scenes in vivid colour. Plus, enjoy the wealth of bonus information and analysis, which expands upon the context of these timeless worlds - building deep, life-long ties to classic tales.
Keywords: Graphic novel; Secundair onderwijs; Shakespeare